The evaluation of sub clinical hypothyroidism in children and adolescents - Aggarwal, Rashmi (International Journal of Research in Medical Sciences, 2025)
Background: Sub clinical hypothyroidism is defined as thyroid stimulating hormone (TSH) >4.2 mIU/ml with a normal level of free T3 and free T4. The prevalence of sub clinical hypothyroidism in adults’ ranges from 1-10%, being higher in the elderly and in females. In children and adolescents, the prevalence is estimated to be less than 2%. Usually children and adolescents with sub clinical hypothyroidism have minimal signs and symptoms and the diagnosis is mostly made incidentally. Objective of the study was evaluation of clinical and etiological characteristics of children and adolescents with sub clinical hypothyroidism and to look at long term consequences in terms of progression to overt hypothyroidism. Methods: Children in the age group of 5-18 years who were referred to the Department of Thyroid and Endocrine Research of Institute of Nuclear Medicine and Allied Sciences (INMAS), from April 2022 to October 2024 with the diagnosis of sub clinical hypothyroidism were recruited for the study. They were followed up for a period of two years. Results: 52 cases of sub clinical hypothyroidism included 33 girls and 19 boys in the age group of 5-18 years. At the end of two year follow up period, in 67.3% of our patients, TSH reverted to normal range spontaneously without any treatment and only 17 patients (32.7%) progressed to overt hypothyroidism and were initiated levothyroxine replacement therapy. Conclusions: Sub clinical hypothyroidism in children is a benign and self-limiting condition with low rate of progression to overt hypothyroidism.